Pengaruh Profitabilitas, Likuiditas, Intensitas Aset Tetap, Intensitas Persediaan, dan Komisaris Independen Terhadap Manajemen Pajak - Medika Purnama Sari Sinaga; Basuki Toto Rahmanto (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
The effective tax rate is the effective corporate tax rate and can be calculated from the total income of taxpayer income divided by profit before taxation. This research aims to analyze the influence profitability, liquidity, capital intensity, inventory intensity, and independent commissioners towards the effective tax rates. The population in this research are all of the mining companies listed on the Indonesian Stock Exchange (IDX) in the period 2015 - 2019. The sample selection by using purposive sampling and obtain a sample of 9 companies or 45 observation data. The data analysis method used in this research is multiple linear regression by using eViews9. The partially result showed that profitability affected negatively towards effective tax rate. Liquidity, capital intensity, inventory intensity, and independent commissioner does not affect towards effective tax rate.